Ionic Liquid Based Nanocarriers for Topical and Transdermal Drug Delivery - Moniruzzaman, M. (Royal Society of Chemistry, 2018)
In the pharmaceutical industry, there are challenges in topical and transdermal administration of drugs, which are sparingly soluble in water and most organic solvents. Ionic liquids (ILs) have been found to be very effective for dissolution of sparingly soluble drugs. However, hydrophilic IL-borne drugs cannot penetrate into or across the skin because of the highly hydrophobic barrier function of the outer skin. In this chapter we report a novel IL-in-oil (IL/o) microemulsion (ME) that is able to dissolve a significant amount of sparingly soluble drug, acyclovir, in the IL core while the continuous oil phase can provide the desired features for topical/transdermal transport through the skin. The ME is composed of a blend of the nonionic surfactants polyoxyethylene sorbitan monooleate (Tween 80) and sorbitan laurate (Span 20), isopropyl myristate (IPM) as an oil phase, and the IL C1mim(MeO)2PO2 (dimethylimidazolium dimethylphosphate) as a dispersed phase. The size and size distribution of the aggregates in the MEs were characterized by dynamic light scattering, showing formation of the nanocarrier in the size range 8-34 nm. In vitro drug permeation studies into and across the skin showed that the IL/o ME increased drug administration compared with other formulations. The safety profile of the new carrier was evaluated using a cytotoxicity assay on the human epidermal model LabCyte. We believe that these IL-assisted nonaqueous MEs can serve as a versatile and efficient nanodelivery system for sparingly soluble drug molecules. Â© The Royal Society of Chemistry 2018.